PRECISION WATER AND NITROGEN MANAGEMENT FOR ENHANCING GROWTH AND YIELD OF AEROBIC RICE UNDER DRIP SYSTEM - S. NARENDER REDDY; M. YAKADRI, B. BHAVANA, P. LAXMINARAYANA, R. MAHENDER KUMAR, K. SUREKHA (The Journal of Research, PJTSAU, 2023)
A Field experiment was conducted at Indian Institute of Rice research (IIRR) during rabi season of 2020 and 2021, with an objective to study the effect of precision water and nitrogen management on growth and yield of aerobic rice under drip system. Treatments included three irrigation management methods- I1 (Drip irrigation 1.5 Epan in Flat bed system); I2 (Drip irrigation 1.5 Epan in Raised bed system) and I3 Surface irrigation (up to saturation) and four precision nitrogen management practices- N1 Recommended practice (RDF)-(120:60:40 N P K kg ha-1); N2 Green seeker (Optical sensor) based N application; N3 (LCC based N application) and N4(No Nitrogen) replicated thrice. Results of experiment revealed that, among all the treatments, surface irrigation with LCC based nitrogen management was more beneficial in enhancing the growth and yield of aerobic rice. Among irrigation methods, higher values of growth parameters (mean of 2020 and 2021) at harvest such as, plant height (82.4 cm), leaf area index (3.98), dry matter accumulation (8344 kg ha-1), tillers m-2 (239), grain yield (4171 kg ha-1) and straw yield (4791 kg ha-1) were observed in surface irrigation which was on par with drip irrigation under raised beds (76.8 cm, 3.66, 7852 kg ha-1, 221, 3738 kg ha-1 and 4209 kg ha-1). Higher values of plant height (85.5 cm), leaf area index (4.46), dry matter accumulation (8802 kg ha-1), tillers m-2 (233), grain yield (4230 kg ha-1) and straw yield (4885 kg ha-1) were recorded under LCC based N application followed by recommended practice among nitrogen management practices. The results of the study implied that, cultivating rice by adopting aerobic system under drip irrigation along with precision nitrogen management with LCC and greenseeker provides an opportunity to save the resources like water and nutrients to produce optimal yields.